PENGARUH MODEL STUDENT FACILITATOR AND EXPLAINING TERHADAP AKTIVITAS DAN HASIL BELAJAR SISWA - Mawadah, Alaina; Irsadi, Andin; Utami, Nur Rahayu (Journal of Biology Education, 2013)
The aim of this research is for knowing the influence of student facilitator and explaining model to the activity and result of students studying about human motion system in SMPN 4 Demak. The population of this research is all students at first semester in VIII classes of SMPN 4 Demak in academic year 2012/2013. The sample used cluster random sampling way, by using this way, it was gotten two classes, The class was class VIII-G (experimental class) using Student Facilitator and Explaining and class VIII-H (control class) using speech and discusion. The calculation of t-test is got of thitung (3,86) > ttabel (2,00),approximately the level of activity of classycal student in experimental class is 90% and control class is 70 %. The classical finalisation of experimentalclass with KKM 70 is 83,33% and control class is 46,67%. Based the result of research could be concluded that Student Facilitator and Explaining model influenced to students activity and learning result about human motion system in SMPN4 Demak. The teacher could apply Student Facilitator and Explainingmodel to increase the students activity and studying result.Â Penelitian ini bertujuan untuk mengetahui pengaruh model Student Facilitator and Expalining terhadap aktivitas dan hasil belajar siswa materi sistem gerak manusia di SMPN 4 Demak. Populasi dalam penelitian ini adalah seluruh siswa kelas VIII Semester I SMPN 4 Demak tahun ajaran 2012/2013. Pengambilan sampel dilakukan dengan teknik cluster random sampling, terpilih 2 kelas sampel yaitu kelas VIII-G (kelas eksperimen) menggunakan model Student Facilitator and Explaining dan kelas VIII-H (kelas kontrol) menggunakan model ceramah dan diskusi biasa. Hasil perhitungan uji t-test menunjukkan bahwa thitung(3,86) > ttabel (2,00), rata-rata tingkat aktivitas klasikal siswa kelas eksperimen sebesar 90%, dan kelas kontrol sebesar 70%. Ketuntasan hasil belajar siswadengan KKM 70 pada kelas eksperimen sebesar 83,33% dan kelas kontrol sebesar 46,67%. Berdasarkan hasil penelitian dapat disimpulkan bahwa model Student Facilitator and Explaining berpengaruh positif terhadap aktivitas dan hasil belajar siswa materi sistem gerak manusia di SMPN 4 Demak. Guru dapat menerapkan model pembelajaran untuk meningkatkan aktivitas dan hasil belajar siswa, seperti model Student Facilitator and Explaining.